Construction of the Giant Panda National Park corridor and restoration of edible bamboo: A case study of from the Chengdu area region - Xing Wang; Yu-Ting Yang; Yan Wu; Yu Xie; Pei Tu; Mei-Ling Liu; Mei-Jiao Zhang; Tao Lu (Ecological Indicators)
Giant pandas (Ailuropoda melanoleuca) serve as flagship species for global biodiversity conservation. Establishing wildlife corridors and introducing edible bamboo species into their understory can enhance giant panda migration and mitigate their vulnerability to human activities and climate change. This study employs the MaxEnt model to analyze habitat suitability for giant pandas and edible bamboo, using the principle of least-cost paths to construct potential ecological corridors while also identifying suitable bamboo species for planting. Results revealed that (1) the habitat suitability index was high in the study region’s central area but low at the periphery, with fragmentation observed, particularly in the northeastern mountains; (2) eight giant panda habitat patches (C1–C8) and nine potential ecological corridors were identified, where C1–C6 patches were small and corridors exhibited low connectivity; and (3) four bamboo species were suitable for planting in the corridors, identified by overlaying corridor layers with bamboo suitability maps. Among the bamboo species, Fargesia spathacea is considered most adaptable, capable of occupying over 40% of the corridor area, followed by Fargesia robusta, recommended for widespread planting in corridor habitats. These findings underscore the importance of strategic habitat management and bamboo restoration in promoting the long-term survival of giant pandas.